An extraordinary variation in origin of inferior alveolar nerve and its clinical significance: a case report - Jha, Shweta; Khorwal, Gitanjali; Kalra, Sunita (International Journal of Research in Medical Sciences, 2017)
Infratemporal fossa is a clinically significant site for delivery of local anaesthesia during dental procedures and maxillofacial surgeries. An extraordinary variation involving formation of inferior alveolar nerve was revealed during routine dissection of infra temporal region for teaching undergraduate medical students. Inferior alveolar nerve was seen to be incongruously originating from two separate roots from the posterior division of mandibular nerve. Furthermore, these two roots of inferior alveolar nerve were divulging unusual relationship with the maxillary artery. Superficial root of inferior alveolar nerve was coursing superficial to second part of maxillary artery and deep root was found to be emerging posterior to this part of maxillary artery. Additionally, deep root was sending a well-defined twig which when traced was found to be communicating with Lingual nerve. This unusual type of variation of Inferior alveolar nerve in this region may result in atypical symptoms of pain, numbness, headaches, interfere with outcome of injection of local anaesthesia and even surgical interventions in the infratemporal fossa.